Innovation and Recycling—Drivers of Circular Economy in EU - Platon, Victor; Pavelescu, Florin Marius; Antonescu, Daniela; Frone, Simona; Constantinescu, Andreea; Popa, Florina (Frontiers in Environmental Science, 2022)
In our days, a growing attention is paid to explain the influence of innovation on recycling. While many studies on this subject have been carried out, it's still needed for more investigations on measuring the effect of innovation on recycling. This paper is dedicated to measuring the intensity of the innovation influence on the recycling within EU member states. The methodology follows the next steps: visualization of data used, determining the stationarity of the time series analyzed, developing a panel model for 28 countries, applying specific statistical tests in case of the two indicators selected. After analyzing the models that resulted and applying Hausman test, the authors concluded that the regression panel with fixed effects is appropriate for our research. Thus, it is possible to show that the influence of the innovation on recycling is moderate and not instantaneous because there is manifested a lag of 2 years. In addition, the Fixed Effects model allows highlighting the heterogeneity that is present among member states. In addition, the authors concluded that the membership of the Euro Area has a positive influence on recycling and on circular economy as well. The article has several originality aspects: it took into account criteria that are not discussed very often as membership of Euro area; it has developed a model that brings quantitative aspects to describe the influence of innovation on recycling, it highlighted the heterogeneity existing among EU member states. Future research direction would be to consider including in the model some other variables as eco-investment.